1989
DOI: 10.1007/bf00442563
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of clozapine in treatment-resistant schizophrenic patients

Abstract: Preliminary results of a non-blinded prospective study of the effect of clozapine on symptomatology and social function in 51 treatment-resistant schizophrenic patients are reported. The mean duration of treatment at the time of this report was 10.3 +/- 8.1 months, median 7.6 months. Overall, 3/51 patients (60.8%) showed at least a 20% decrease in total BPRS, a criterion of improvement in the study of Kane et al. (1988). Four of 51 (7.8%) had at least a 50% decrease in total BPRS. Improvements in both positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
86
0
4

Year Published

1989
1989
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(99 citation statements)
references
References 9 publications
9
86
0
4
Order By: Relevance
“…The proportion of subjects who improved in this study (68%, N=34 of 50) is high but still consistent with data reported in other follow-up studies (9,14). The present data were collected with the clinical and research (rating) staff aware that clozapine was the treatment drug, which creates a possible expectancy bias toward response.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The proportion of subjects who improved in this study (68%, N=34 of 50) is high but still consistent with data reported in other follow-up studies (9,14). The present data were collected with the clinical and research (rating) staff aware that clozapine was the treatment drug, which creates a possible expectancy bias toward response.…”
Section: Discussionsupporting
confidence: 93%
“…In the U.S. multicenter clozapine study (8), improvement continued to increase steadily in the clozapine-treated patient group for the entire 6-week period, with no plateau in response measures. This has led to a concern that late response might be a characteristic of clozapine treatment (9).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the published literature addressing these two differing perspectives has been limited principally to open-label studies (33,34). The present investigation contained several important methodologic improvements: 1) the trial was blind, 2) it contained both an active-drug and a placebo comparison group, 3) the dosing permitted flexibility within a range in order to optimize each individual's dose, 4) the protocol excluded or controlled for other concomitant drug use, 5) it did not permit concurrent nonpharmacologic treatments, and 6) the data analysis strategy included a novel statistical method to differentiate direct versus indirect (or secondary) change in negative symptoms across the randomly assigned treatment groups.…”
Section: Discussionmentioning
confidence: 99%